Kajian Hukum Hak Atas Tanah Masyarakat Long Midang Yang Memiliki Tanah Melebihi Ketentuan Dalam Undang-Undang RI Nomor 56 No.56 PRP Tahun 1960 Tentang Penetapan Luas Tanah Pertanian - Asprila, Steven Daustina; Rehas, Abdul Mukmin (Yuriska: Jurnal Ilmiah Hukum, 2019)
The land is a source of life for living creature, whether human, animal or plant. Humans live and live on the ground and these the land to source life by planting plants that produce food. Considering the importance of land because it can produce natural resources that are very beneficial for many people, the government needs to be related. Landis also one of the factors of production that are vital for human life and development in a nation. An increase in the volume of development within a country, eroding the importance of land for agriculture. Population growth requires a large area, resulting in reduced or reduced land supply. Then the government made law number 56 of PRP in 1960 concerning the stipulation of the area of agricultural land carried out by the long midrange community was hereditary. And at the time of the process of returning the rights to the community's land long midrange program, there was a problem that the long midrange community did not agree with the program because the long midrange community did not want a portion it the agricultural land was taken by the government. And in general, agricultural land controlled by the people in long midrange is used for agricultural land because the potential of natural resources here is quite abundant and even then that is used by the people in long midrange as agricultural lands, such as making rice field, plantations, fields, and still many more are use our exciting community. But the community does not know of the minimum and maximum limit or agricultural land they community.